Contact kinematics of patient-specific instrumentation versus conventional instrumentation for total knee arthroplasty - Broberg, Jordan S.; Naudie, Douglas D.R.; Howard, James L.; Vasarhelyi, Edward M.; McCalden, Richard W.; Teeter, Matthew G. (The knee, 2020)
The goal was to evaluate the joint contact kinematics of total knee arthroplasties implanted using patient-specific instrumentation (PSI) compared to conventional instrumentation (CI). We hypothesized that use of PSI would not significantly alter contact kinematics. The study was a prospective randomized controlled trial, with equal allocation of fifty patients to PSI and CI groups. At two years post-operation, patients underwent weight-bearing stereo X-ray examinations at 0°, 20°, 40°, 60°, 80°, and 100° of flexion. The shortest tibiofemoral distance on each condyle determined the contact location. Magnitude of the shortest distance was measured and condylar separation was analyzed using thresholds of 0.5 and 0.75 mm. Kinematic measurements derived from the shortest distance included anteroposterior (AP) translation, excursion, axial rotation, and paradoxical anterior motion. Pivot position and cam/post contact were also investigated. There were no differences (p > 0.05) in medial and lateral AP contact locations, excursions, and magnitude of anterior motion, or in axial rotation, pivot patterns, frequency of cam/post engagement, frequency of medial anterior motion, and condylar separation at a 0.75 mm threshold. Significant differences were found in frequency of lateral anterior motion (p = 0.048) and condylar separation at a 0.5 mm threshold (p = 0.010). Both groups displayed typical kinematics for a fixed-bearing posterior-stabilized implant. We found no major differences in knee kinematics between PSI and CI groups, which suggest that PSI does not provide a significant kinematic advantage over conventional instruments.